2016
DOI: 10.1099/jgv.0.000639
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of antibiotic resistance genes in environmental bacteriophages

Abstract: The ecosystem is continuously exposed to a wide variety of antimicrobials through waste effluents, agricultural run-offs and animal-related and anthropogenic activities, which contribute to the spread of antibiotic resistance genes (ARGs). The contamination of ecosystems with ARGs may create increased opportunities for their transfer to naive microbes and eventually lead to entry into the human food chain. Transduction is a significant mechanism of horizontal gene transfer in natural environments, which has tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 55 publications
0
25
0
1
Order By: Relevance
“…It is well known that phages can transfer genetic components between bacterial isolates, but the role of phages in disseminating antimicrobial resistance genes is still a matter of debate (Colavecchio et al, 2017 ; Enault et al, 2017 ). Nonetheless, some studies have found that phages are able to transfer genes conferring resistance to aminoglycosides ( aadA, aphA1, strA, strB ), β-lactams ( bla CMY−2 , bla CTX−M−9 , bla OXA−2 , bla OXA−20 , bla PSE−1 , bla TEM ), chloramphenicol ( floR ), or tetracycline ( tet (A), tet (B), tetG, tetO, tetW ) via transduction (Zhang and LeJeune, 2008 ; Colomer-Lluch et al, 2014 ; Bearson and Brunelle, 2015 ; Ross and Topp, 2015 ; Shousha et al, 2015 ; Anand et al, 2016 ). In addition, a recent study has identified that two E. coli phages could promote the transformation of plasmids carrying antimicrobial resistance genes (Keen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that phages can transfer genetic components between bacterial isolates, but the role of phages in disseminating antimicrobial resistance genes is still a matter of debate (Colavecchio et al, 2017 ; Enault et al, 2017 ). Nonetheless, some studies have found that phages are able to transfer genes conferring resistance to aminoglycosides ( aadA, aphA1, strA, strB ), β-lactams ( bla CMY−2 , bla CTX−M−9 , bla OXA−2 , bla OXA−20 , bla PSE−1 , bla TEM ), chloramphenicol ( floR ), or tetracycline ( tet (A), tet (B), tetG, tetO, tetW ) via transduction (Zhang and LeJeune, 2008 ; Colomer-Lluch et al, 2014 ; Bearson and Brunelle, 2015 ; Ross and Topp, 2015 ; Shousha et al, 2015 ; Anand et al, 2016 ). In addition, a recent study has identified that two E. coli phages could promote the transformation of plasmids carrying antimicrobial resistance genes (Keen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study focuses on the prevalence of ARGs in bacteriophages, ubiquitous bacterial viruses that have been reported in diverse environments 21,22,2931 , in human 25 and animal feces 26 , and more recently in vegetables and agricultural soils 28,32 . Bacteriophages facilitate ARG transmission between bacteria, as transduction does not require direct contact between “donor” and “recipient” cells, although the transfer mechanism is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…While novel gene uptake by transduction is generally considered important (Ross and Topp, 2015), there are mixed views as to the significance of ARGs within environmental bacteriophages on the development of environmental AMR due to misinterpretation from sequence information (Enault et al, 2017) and given the high concentration of active host cells generally needed to provide interactions, as seen in clinical environments (Stanczak-Mrozek et al, 2015). Nonetheless, environmental transduction has been demonstrated (Anand et al, 2016) and the persistence of ARGs is clearly influenced by the greater persistence of bacteriophages in the environment versus ARB (Calero-Cáceres and Muniesa, 2016) or novel superspreaders (Keen et al, 2017). Therefore, sanitation processes that are focused on enteric virus nucleic acid elimination may also be effective in reducing the release and presence of bacteriophage/plasmid-mediated environmental ARGs.…”
Section: Presence and Transfer Of Extracellular Genes Within The Envimentioning
confidence: 99%